PD-1-mAb Plus Regimen in the First and Second Lines of Advanced and Unresectable Biliary Tract Carcinoma: A Real-World, Multicenter Retrospective Analysis - Wang F; Wang FH; Sun K; Jiang C; Peng S; Xu LX; Kuang M; Guo GF; Chen SL (Dove Medical Press, 2022)
Fang Wang,1,* Feng-Hua Wang,2,3,* Kaiyu Sun,4,* Chang Jiang,2,5 Sui Peng,6 Li-Xia Xu,1 Ming Kuang,7 Gui-Fang Guo,2,5,8 Shu-Ling Chen9 1Department of Oncology, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People's Republic of China; 2State Key Laboratory of Oncology in South China, The Sun Yat-Sen University Cancer Center, Guangzhou, People's Republic of China; 3Department of Oncology, The Sun Yat-Sen University Cancer Center, Guangzhou, People's Republic of China; 4Department of Gastrointestinal Surgery, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People's Republic of China; 5Collaborative Innovation Center for Cancer Medicine, The Sun Yat-Sen University Cancer Center, Guangzhou, People's Republic of China; 6Institute of Precision Medicine, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People's Republic of China; 7Department of Liver Surgery, Center of Hepato-Pancreato-Biliary Surgery, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, People's Republic of China; 8VIP Department, Sun Yat-sen University Cancer Center, Guangzhou, People's Republic of China; 9Institute of Diagnostic and Interventional Ultrasound, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Shu-Ling Chen; Gui-Fang Guo, Email chenshling@mail.sysu.edu.cn; guogf@sysucc.org.cnIntroduction: Advanced biliary tract carcinoma (BTC) has a poor prognosis and few treatment options. We compared the efficacy of the PD-1 monoclonal antibody (PD-1-mAb) combined regimens with the standard chemotherapy in the first-line and second-line treatment of advanced BTC.Methods: We retrospectively assessed the patients with advanced BTC, who received treatment at the First Affiliated Hospital of Sun Yat-Sen University and the Sun Yat-Sen University Cancer Center. The patients were treated with PD-1-mAb combined regimens or standard chemotherapy at the first line or treated with PD-1-mAb combined regimens or systematic therapy at the second line. Further subgroup analyses were assessed to identify superior regimens.Results: This study included 210 patients. The first-line PD-1-mAb combination group (n = 83) achieved longer median PFS (mPFS) (7.3 vs 5.3 months, p=0.001) and median OS (mOS) (15.6 vs 11.4 months, p=0.002) than the first-line standard chemotherapy group (n=76). Similarly, the second-line PD-1-mAb combination group (n=50) yielded longer mPFS (6.1 vs 2.6 months, p< 0.001) and mOS (11.7 vs 7.2 months, p=0.008) than the second-line systematic therapy group (n=51). Subgroup analyses showed that the PD-1-mAb combined with TKI group achieved better mPFS than the chemotherapy group whether in the first-line (HR = 0.468, p=0.005) or the second-line setting (HR = 0.45, p=0.009), but did not achieve superiority in mOS (both p> 0.05). Compared with the chemotherapy group, the PD-1-mAb combined with chemotherapy group achieved longer mOS (HR = 0.53, p=0.023) in the first-line setting and longer mPFS in the second-line setting (HR = 0.54, p=0.044).Conclusion: The PD-1-mAb combination therapy is superior to the standard chemotherapy in advanced or unresectable BTC, whether as a first-line or second-line treatment. Among the combination therapy, both the PD-1-mAb combined with TKI and combined with standard chemotherapy were promising options for advanced BTC patients.Keywords: biliary tract carcinoma, PD-1-mAb, PD-1 plus anti-angiogenesis TKI, PD-1 plus chemotherapy, the first-line chemotherapy, the second-line chemotherapy